Measurement of Helium Leakage Rates through Closures of Dangerous Goods Packagings for the Assessment of Potentially Explosive Mixtures in Freight Containers. (7th October 2015) - Schlick‐Hasper, Eva; Seidler, Oliver; Goedecke, Thomas; Kraume, Matthias
<x xml:space="preserve">Abstract</x> The objective was to find out whether an explosive atmosphere can be created in a freight container by gaseous leakage flow of vapour‐air‐mixture through leaks in the closures of dangerous goods packagings filled with hazardous liquids. Because of high temperatures during intercontinental carriage, there is a gauge pressure in the free vapour phase inside the packagings which can cause a gaseous leakage flow. Two different methods were applied: Helium limit leakage rates for 23 quantitatively important hazardous liquids concerning their lower explosion limit (LEL) were calculated for a worst case transport scenario (Method 1). Helium leakage rates of five closure types of dangerous goods packagings with volumes of approximately 6 l were measured using the pressure technique by accumulation (Method 2). All types of closures of steel packagings were uncritical. The maximum measured leakage was 33% of the limit leakage rate. The leakage rates of screw closures of plastic jerricans can exceed the LEL if there are production‐related patterns such as non‐concentricity of the closures and flashes on the neck. Especially for plastic packagings it is important to minimize gaseous leakage flow, because an explosive atmosphere can also be reached by permeation of the individual filling substance or by a combination of both effects. For the assessment of potentially explosive mixtures in freight containers, both mass transfer mechanisms have to be taken into account. Copyright © 2015 John Wiley & Sons, Ltd.